Spectroscopic Atlas of Atmoshperic Microwindows in the Middle Infra-Red - Meier, Arndt; Toon, Geoffrey C.; Rinsland, Curtis P.; Goldman, Aaron; Hase, Frank (Swedish Institute of Space Physics, 2004)
This second edition of the infrared microwindow atlas contains a collection of spectral mi- crowindows commonly used or recently suggested for ground-based, high resolution, infrared solar absoption spectroscopy. These solar observations are aimed at quantifying the abun- dance of trace species in the terrestrial atmosphere. A microwindow is a narrow spectral interval that allows to observe a specific atmospheric absorber unambiguously. The width of a microwindow may vary but is typically between 0.1 and 5cm−1 wide, though wider windows may in some cases be used or multiple narrow windows may be combined in any particular retrieval. The spectra and corresponding simulations shown in the figures are representing solar absorption spectra recorded in Arctic Scandinavia on 15/Mar/1997 (500 to 4370cm −1 ) and 01/Apr/1998 (3950 to 9000cm−1 ). The printed atlas discusses close to 250 microwindows. Lively discussions at the annual meetings of the infrared working group of the Network for Detection of Stratospheric Change (NDSC) have demonstrated a continued high interest in an up-to-date reference work on commonly used microwindows in the field of infrared ground- based remote sensing. The present work attempts to summarise the collective knowledge that the NDSC community has on this topic. The work of many past and present experts in the field have contributed to this compilation and the authors wish to express their thanks to all of them. At present, no recommendations on the optimum selection of microwindows for individual species are provided. That task is beyond the scope of the present work and also depends on the observation site and instrumental parameters. However, where inconsistencies be- tween observation and simulations are striking, or in cases where common pitfalls have been reported, we provide comments to highlight potential problems. Several microwindows have been noted previously in the literature, and we have included a list of references citing their use. We are aware that the current edition is ...